How Does Information Sharing of a Supervisor Influence Proactive Change Behavior of an Employee? The Chain Mediating Role of Family-Like Employee–Organization Relationship and Relationship Energy - Zhu, Xiao-Xia; Li, Chun; Wang, Xiao-Ling; Liu, Jun-Na; Xia, Senmao (Frontiers in Psychology, 2021)
Employee’s proactive change behavior is the key to promoting organizational innovation. However, the proactive change has a certain risk, and many employees are unwilling to implement initiatively. How to promote the occurrence of employee’s proactive change behavior has become a hot issue in the theoretical and practical areas. Based on the self-disclosure theory, this study uses the questionnaire survey method, a total of 32 items, and uses the Likert five point scale (1 = strongly disagree, 5= strongly agree), with Mplus and SPSS statistical software to analyze the impact mechanism of supervisors’ work-related information sharing on employee’s proactive change behavior through structural equation model. The regulatory effect of leaders' non work information sharing is analyzed by latent regulatory structural equation method. The conclusions are as follows: supervisors’ work-related information sharing positively influences family-like employee-organization relationship of employees; family-like employee-organization relationship and relationship energy play serial mediating roles in the relationship between supervisors’ work-related information sharing and employee’s proactive change behavior; supervisors' non-work information sharing moderates the serial mediating path by enhancing the positive influence of supervisors’ work-related information sharing on family-like employee-organization relationship. Theoretically, this study has complemented and enriched the research on the influence mechanism between supervisors' information sharing and employee’s proactive change behavior. Practically, this study has important implications for supervisors to promote employee’s proactive change behavior by sharing work-related information and non-work information with employees.